Through the Eyes of the Delusional Ones - Awale, Rasha (Hungarian Journal of English and American Studies, 2021)
Book review: Hanson, Victor Davis. The Case for Trump. New York: Hachette Book Group Inc., 2019. 355 pages. ISBN 978-5416-7353-3. Ebook. 16.81.